The Role of the “EcoMasjid” Program in Jakarta in the Development of Awareness of Eco-Friendly Living Culture - Purwanto, Heru; Imawan, Ficky Augusta; Reynold, Wiliam (UI Scholars Hub, 2024)
Background: The acceleration of the social and economic today has produced a new phenomenon and challenge: Environmental crisis. As a result, various studies from diverse disciplines and perspectives, seek to carry out various mitigative and preventive analyses and innovations. One of them is through a religious approach that is believed to influence the movement, especially in the context of Indonesia with a Muslim population of 240.62 million as the majority population in Indonesia and a total of 299,692 mosques. Aims: This study seeks to study the role of one of the efforts made by the Indonesian Ulema Council (MUI) in the